2012
DOI: 10.1158/0008-5472.can-12-2424
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Contributes to Melanoma Growth and Metastasis via Regulation of NFAT1 and Autotaxin

Abstract: Melanoma is the deadliest form of skin cancer in which patients with metastatic disease have a five year survival-rate of less than 10%. Recently the over expression of a beta galactoside binding protein, galectin-3 (LGALS3), has been correlated with metastatic melanoma in patients. We have previously shown that silencing galectin-3 in metastatic melanoma cells reduces tumor growth and metastasis. Gene expression profiling identified the pro-tumorigenic gene autotaxin (ENPP2) to be down regulated after silenci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 46 publications
(60 reference statements)
2
64
1
2
Order By: Relevance
“…In our study, we found that VEGF-C largely lost its ability to promote SiHa cell invasion when Gal-3 expression was silenced, suggesting a crucial role of Gal-3 in VEGF-C-promoted cervical cancer cell invasiveness. This is consistent with other studies showing that Gal-3 overexpression is associated with increased invasiveness of melanoma, ovarian, thyroid and colorectal cancer cells [12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found that VEGF-C largely lost its ability to promote SiHa cell invasion when Gal-3 expression was silenced, suggesting a crucial role of Gal-3 in VEGF-C-promoted cervical cancer cell invasiveness. This is consistent with other studies showing that Gal-3 overexpression is associated with increased invasiveness of melanoma, ovarian, thyroid and colorectal cancer cells [12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
“…Inhibition of galectin expression, using siRNA or antisense sequences, showed significant results in colon [233], ovarian [234], esophageal [235], hepatocarcinoma [236], glioma [237], glioblastoma [238], and melanoma [239] cell lines. Anti-galectin mAbs and Gal-3 recombinant were also effective in vitro studies with diverse cell lines [240-242].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, galectin-3 reduces glioma cell migration (121). In general, however, galectin-3 (107) is mostly associated with increased invasive behavior in most cancer cell types tested (94,95,117,(122)(123)(124)(125)(126), supporting the view that targeting this galectin might be a promising avenue for the treatment of many types of cancer. Whether this is also true for other galectins has to be determined.…”
Section: Galectin (%) Cellular --------------------------------------mentioning
confidence: 95%